2020
DOI: 10.1002/ejp.1607
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral and central nervous system correlates in fibromyalgia

Abstract: Background: Fibromyalgia (FM) is a syndrome characterized by altered pain processing at central and peripheral level, whose pathophysiologic mechanisms remain obscure. We aimed at exploring the structural changes of peripheral nociceptor measured by skin biopsy, the functional changes of central nociceptive pathway assessed by laser evoked potentials (LEP), and their correlation with clinical features and comorbidities.Methods: Eight-one patients diagnosed with FM underwent skin biopsies with quantification of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 59 publications
2
18
0
Order By: Relevance
“…56,57,64 A recently published study by Vecchio et al showed an association between a reduction of intraepidermal nerve fiber density at the thigh and reduced laser-evoked habituation index in 81 patients with FMS. 63 The authors concluded that central sensitization may be the most relevant mechanism in FMS. We defined the following parameters as signs for central sensitization: decreased MPT and/or increased MPS and/or the presence of DMA.…”
Section: Central Sensitizationmentioning
confidence: 99%
“…56,57,64 A recently published study by Vecchio et al showed an association between a reduction of intraepidermal nerve fiber density at the thigh and reduced laser-evoked habituation index in 81 patients with FMS. 63 The authors concluded that central sensitization may be the most relevant mechanism in FMS. We defined the following parameters as signs for central sensitization: decreased MPT and/or increased MPS and/or the presence of DMA.…”
Section: Central Sensitizationmentioning
confidence: 99%
“…Actual concepts of FMS suggest a multifactorial pathology including disruption of inhibitory pain modulation (Uygur‐Kucukseymen et al., 2020), altered BDNF expression (Polli et al., 2020), central sensitization (Vecchio et al., 2020), peripheral neuropathies (Leinder et al., 2016), post‐traumatic stress disorder and corresponding behavioural features (Conversona et al., 2019) as well a variety of psychological and social stress factors and chronic fatigue (Haeuser, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The results proved our hypothesis. Relevant researches data were reported that the pathogenesis of FM involves disciplines of central nervous system, automatic nervous system, neurotransmitter, hormone secretion, immune system, genetics and psychiatry [29][30][31][32][33][34]. Among them, neurotransmitter of 5-HT and cytokines such as IL-6 and IL-8 were closely related to the development of FM [35][36][37][38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%